Antibody PEGylation in bioorthogonal pretargeting with trans-cyclooctene/tetrazine cycloaddition: in vitro and in vivo evaluation in colorectal cancer models. Issue 1 (December 2017) - Rondon, Aurélie; Ty, Nancy; Bequignat, Jean-Baptiste; Quintana, Mercedes; Briat, Arnaud; Witkowski, Tiffany; Bouchon, Bernadette; Boucheix, Claude; Miot-Noirault, Elisabeth; Pouget, Jean-Pierre; Chezal, Jean-Michel; Navarro-Teulon, Isabelle; et al.
Abstract Bioorthogonal chemistry represents a challenging approach in pretargeted radioimmunotherapy (PRIT). We focus here on mAb modifications by grafting an increase amount oftrans -cyclooctene (TCO) derivatives (0 to 30 equivalents with respect to mAb) bearing different polyethylene glycol (PEG) linkers between mAb and TCO (i.e. PEG0 (1 ), PEG4 (2 ) and PEG12 (3 )) and assessing their functionality. We used colorectal xenograft (HT29/Ts29.2) and peritoneal carcinomatosis (A431-CEA-Luc/35A7) as tumor cells/mAbs models and fluorescent tetrazines (TZ). MALDI-TOF MS shows that grafting with2, 3 increases significantly the number of TCO per mAb compared with no PEG.In vitro immunofluorescence showed that Ts29.2 and 35A7 labeling intensity is correlated with the number of TCO when using1, 3 while signals reach a maximum at 10 equivalents when using2 . Under 10 equivalents conditions, the capacity of resulting mAbs-1–3 for antigen recognition is similar when reported per grafted TCO and comparable to mAbs without TCO.In vivo, on both models, pretargeting with mAbs-2, 3 followed by TZ injection induced a fluorescent signal two times lower than with mAbs-1 . These findings suggest that while PEG linkers allow a better accessibility for TCO grafting, it might decrease the number of reactive TCO. In conclusion, mAb-1 represents the best candidate for PRIT.